Acquired multiple mutations ALK I1171N, L1196M and G1202R mediate lorlatinib resistance in EML4-ALK-rearranged malignant pleural mesothelioma: a case report - Hu, Jia (Ther Adv Respir Dis, 2020)
EML4-ALK rearranged malignant pleural mesothelioma (MPM) is rare and its responses to anaplastic lymphoma kinase (ALK) inhibitors, including alectinib and lorlatinib, remain unexplored. In this case report, we describe a patient with EML4-ALK-rearranged stage IIIB MPM who was administered with alectinib and lorlatinib as first-line and fourth-line therapy, respectively. He had remarkable response evaluated as partial response on both regimens lasting approximately 3.5 months on each regimen. His plasma samples were collected during the treatment course and submitted for targeted sequencing to understand the molecular mechanisms of his therapeutic resistance. Sequencing analysis revealed the emergence of ALK I1171N and L1196M at alectinib progression. Meanwhile, ALK I1171N, L1196M, and G1202R mutations were identified at lorlatinib progression, wherein L1196M is confirmed to be in cis to G1202R. We speculate that these multiple mutations synergistically mediated his resistance to both alectinib and lorlatinib. Our report describes the detection of EML4-ALK rearrangement in a patient with MPM who had remarkable therapeutic response with ALK inhibitors. Moreover, our case also revealed acquired mechanisms of lorlatinib resistance mediated by multiple mutations ALK I1171N, L1196M, and G1202R, contributing an incremental step to our understanding of the complexity of acquired resistance mechanisms in sequential ALK inhibitor therapy. The reviews of this paper are available via the supplemental material section.